Folic Acid Supplementation for Blood Pressure Reduction in Hypertension: A Meta-Analysis - Harqiqi, Andreafika Kusumaningtyas; Evi Supriadi (HM Publisher, 2024)
Background: Hypertension is a major risk factor for cardiovascular disease. While antihypertensive medications are the cornerstone of treatment, adjunctive therapies like folic acid supplementation have gained attention for their potential to lower blood pressure. This meta-analysis aims to comprehensively assess the impact of folic acid supplementation on blood pressure in hypertensive individuals. Methods: A systematic search of electronic databases (PubMed, Embase, Cochrane Library) was conducted from January 2018 to December 2023 to identify randomized controlled trials (RCTs) evaluating the effect of folic acid supplementation on blood pressure in adults with hypertension. Data on systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were extracted. A random-effects model was used to pool data, and heterogeneity was assessed using the I² statistic. Results: Twenty-three RCTs involving 2,853 hypertensive participants were included. Folic acid supplementation was associated with a significant reduction in SBP (mean difference [MD] -2.93 mmHg, 95% confidence interval [CI] -4.11 to -1.75, p < 0.00001), DBP (MD -1.87 mmHg, 95% CI -2.63 to -1.11, p < 0.00001), and MAP (MD -2.21 mmHg, 95% CI -3.01 to -1.41, p < 0.00001) compared to placebo or control. Subgroup analyses revealed that the blood pressure-lowering effect of folic acid was more pronounced in individuals with low baseline folate levels, those with higher baseline blood pressure, and in studies with longer durations of supplementation. Conclusion: Folic acid supplementation appears to be a safe and effective adjunctive therapy for reducing blood pressure in hypertensive individuals. These findings support the potential role of folic acid in improving cardiovascular outcomes in this population.